Approximational Projection of a Network with an Arbitrary Structure - Usenko, Valerii; Kodak, Olga; Usenko, Iryna (International Journal of Engineering and Technology, 2018)
Improving the efficiency of the functioning of the engineering networks of cities involves solving the issues of expanding and deepening the process of studying the interconnection of its components.An approximate definition of the property of the network structure's connectivity belongs to the conceptual class of diminishing the dimension of the multiplicity of system parameters. It studies the structures of networks with arbitrary reliability of its constituent parts. The reflection of the reliability values of the components of a redundant engineering network structure is appropriate for large-scale networks. The multiplicity of the network is projected onto the subspace of its parameters with variable values of the argument of the function of the integrity of the connectivity.Â Â